Observations on the Law of Implied Warranty of Quality in Missouri: 1960 - Edmond R. Anderson Jr. (Washington University Law Quarterly, 1960)
Recent cases indicate a strengthened and extended law of implied warranty of quality in Missouri. Two of these cases deserve close consideration: Ross v. Philip Moris Co., 164 F. Supp. 683 (W.D. Mo. 1958), modified, No. 9494, W.D. Mo., Oct. 22, 1959; Midwest Game Co. v. M.F.A. Milling Co., 320 S.W. 2d 547 (Mo. 1959).
Keywords: Warranty